Psychophysiological synchrony during verbal interaction in romantic relationships - Coutinho, Joana (2019)
Previous studies about romantic relationships have shown that the reciprocal influence between partners occurs not only at the behavioral and socio‐emotional levels, but also at the psychophysiological level. This reciprocal influence is expressed in a pattern of physiological synchrony between partners (i.e., coordinated dynamics of the physiological time series). The main aim of the present study was to explore the presence of a pattern of physiological synchrony in electrodermal activity (EDA) during a couple interaction task. A second objective was to compare the synchrony levels during a negative interaction condition versus a positive interaction condition. Finally, we analyzed the association between synchrony and self‐perception of empathy, dyadic empathy, and relationship satisfaction. Thirty‐two couples (64 individuals) participated in this study. Each couple performed a structured interaction task while the EDA of both partners was being registered. The quantification of synchrony was based on the cross‐correlation of both members' EDA time‐series. In order to control for coincidental synchrony, surrogate datasets were created by repeatedly shuffling the original data of spouses X and Y of a dyad and computing synchronies on the basis of the shuffled data (pseudosynchrony values). Our results confirmed the presence of significant EDA synchrony during the interaction. We also found that synchrony was higher during the negative interactions relative to the positive interactions. Additionally, physiological synchrony during positive interaction was higher for those couples in which males scored higher in dyadic empathy. The clinical implications of these findings are discussed.